Genetics of toll like receptor 9 in ANCA associated vasculitides. Issue 5 (16th April 2013) - Husmann, C A; Holle, J U; Moosig, F; Mueller, S; Wilde, B; Cohen Tervaert, J W; Harper, L; Assmann, G; Gross, W L; Epplen, J T; Wieczorek, S
Abstract : Objectives: To investigate the contribution of genetic polymorphisms of toll like receptor (TLR) 9 and related genes on the susceptibility and clinical manifestation of anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitides (AAV). Methods: Four single nucleotide polymorphisms (SNPs) in TLR9 were genotyped in 863 German AAV cases and 1344 healthy controls. Significant results were replicated in a cohort of 426 Dutch and British AAV cases. 11 polymorphisms in TLR9 related genes were studied concomitantly. Results: A strong association of TLR9 genotypes and haplotypes with granulomatosis with polyangiitis was observed as well as a contrariwise association with microscopic polyangiitis. The association was confirmed when cases were compared according to ANCA status rather than to clinical entity. This was partly replicated in the second cohort leading to a striking overall difference in TLR9 allele/haplotype frequencies between proteinase 3 (PR3) ANCA+ and myeloperoxidase (MPO) ANCA+ cases (p=0.00000398, pc=0.000016, OR 1.68 (95% CI 1.35 to 2.1) for rs352140; p=0.000011, pc=0.000044, OR 1.64 (95% CI 1.31 to 2.04) for a 3-SNP haplotype). No significant association or epistatic effect was detected for TLR9 related genes: interleukin 6, interleukin 23 receptor, myeloid differentiation primary response 88, TNF receptor-associated factor 6, interleukin-1 receptor-associated kinase 4, discs large homolog 5 and nucleotide-binding oligomerisation domain containing 2. Conclusions: We provide further evidence that PR3-ANCA+ AAV differs genetically from MPO-ANCA+ AAV. TLR9 signalling may be involved in disease pathology, favouring models of infectious agents triggering AAV development.